INDIKASI PENYALAHGUNAAN DISCRETIONARY FUND DALAM ANGGARAN PENDAPATAN DAN BELANJA DAERAH MENJELANG PEMILUKADA 2015 - Winoto, Agus Hadi; Falikhatun, Falikhatun (Jurnal Akuntansi dan Keuangan Indonesia, 2015)
This study aims to investigate the possibility of any indication of misuse of discretionary funds in the budget, and to obtain empirical evidence on the factors of budget capability and political motives that affect the proportion of these funds before the local election in 2015. The study was conducted in 143 districts/cities in Indonesia in 2015 which implement the local election simultaneously. The results using t-test showed that there was no different proportion of discretionary funds before and ahead of the local election in 2015. This implies that there is no indication of misuse of grant and social aid before the local election in 2015. The results of multiple regression analysis showed that the fiscal capacity factor (fiscal space) and political factors affect the size of proportion of discretionary funds (grants and social aid) before the local election in 2015. The larger the local government fiscal space, the greater the allocation of its discretionary funds. Incumbents are more likely to use discretionary funds to lure prospective voters to reelect in the local election 2015 than non-incumbent regional head.